GEOCHEMISTRY AND TECTONIC SIGNIFICANCE OF BASALTS IN THE DARE-ANAR COMPLEX: EVIDENCE FROM THE KAHNUJ OPHIOLITIC COMPLEX, SOUTHEASTERN, IRAN (Journal of Sciences, Islamic Republic of Iran)
The Kahnuj ophiolitic complex, a part of the Jazmurian ophiolitic belt, is located on the western boundary of the Jazmurian depression and is bounded by two major fault systems. There is a well-preserved, ophiolite pseudostratigraphy of early Cretaceous to early Palaeocene age and has a bearing on the Mesozoic development of southeastern part of Iran and adjacent region. The Kahnuj ophiolitic complex consists mainly of lava flows and pillow lavas with intermittent pelagic limestones, sheeted dykes, gabbros, and plagiogranites, with subordinate ultramafic rocks. Structurally, the complex is extensively faulted and fractured. The volcanic rocks have undergone low grade alteration and metamorphism, exhibiting greenschist facies assemblages. The basalts exhibit variable enrichment in LFS elements (Sr, K, Ba) relative to HFS elements (Ti, Zr, Y, Nb, P). The basalts are characterized by low Zr/Y (3.24-5.03), Th/Ta (1.29-2.55), La/Nb (1.43-2.15) and Nb/Y (0.12-0.2) ratios, relatively low TiO2 and P2O5, and progressively enriched normalized patterns and increased Ce and Th values. Based on chemical discrimination parameters, the Dare-Anar basalts were originally developed in a back-arc basin and are representative of supra-subduction zone Tethyan ophiolites.